THE RELATIONSHIP BETWEEN THE EIGHT-GRADE STUDENTS' VOCABULARY MASTERY AND THEIR WRITING ACHIEVEMENT AT SMP PGRI PEDAMARAN - Yuris Tri Harli; Dewi Sartika; Kiki Rizki Amelia (Language and Education Journal, 2024)
In the world of language development and academic achievement, the relationship between vocabulary mastery and writing power is critical. Recognizing the tremendous impact of students' lexical command on their ability to compose descriptive texts is critical for educators seeking to improve language teaching. As a result, the purpose of this study is to investigate the possible relationship between students' English vocabulary mastery and their ability to write descriptive texts at SMP PGRI Pedamaran. This inquiry provides useful insights into the underlying aspects that support excellent English writing. Utilizing a purposive sampling strategy, three classes comprising 72 students were chosen as the sample group. Data collecting included delivering multiple[1]choice vocabulary exams as well as essay-based writing tests. The Pearson Product Moment correlation approach was utilized to conduct further study. The findings show a substantial relationship between students' English vocabulary ability and their ability for descriptive writing at SMP PGRI Pedamaran. The estimated correlation coefficient (r) of 0.26 was more than the crucial value (r-table) of 0.23 at a significance level (p) of less than 0.05, indicating a weak correlation. This emphasizes the importance of vocabulary in generating descriptive texts, as well as its significance in language proficiency. As a result, vocabulary mastery emerges as a critical determinant in students' ability to successfully explain descriptive narratives, emphasizing its intrinsic value in the writing process